A heterozygous mutation in tubulin, beta 2B ( Tubb2b ) causes cognitive deficits and hippocampal disorganization. (3rd October 2016) - Stottmann, Rolf W.; Driver, Ashley; Gutierrez, Arnold; Skelton, Matthew R.; Muntifering, Michael; Stepien, Christopher; Knudson, Luke; Kofron, Matthew; Vorhees, Charles V.; Williams, Michael T.
Abstract : Development of the mammalian forebrain requires a significant contribution from tubulin proteins to physically facilitate both the large number of mitoses in the neurogenic brain (in the form of mitotic spindles) as well as support cellular scaffolds to guide radial migration (radial glial neuroblasts). Recent studies have identified a number of mutations in human tubulin genes affecting the forebrain, including TUBB2B . We previously identified a mouse mutation in Tubb2b and we show here that mice heterozygous for this missense mutation in Tubb2b have significant cognitive defects in spatial learning and memory. We further showed reduced hippocampal long‐term potentiation consistent with these defects. In addition to the behavioural and physiological deficits, we show here abnormal hippocampal morphology. Taken together, these phenotypes suggest that heterozygous mutations in tubulin genes result in cognitive deficits not previously appreciated. This has implications for design and interpretation of genetic testing for humans with intellectual disability disorders. Abstract : A missense mutation in tubulin beta, 2B leads to morphological changes in the hippocampus and cognitive deficits.